From Compliance to Self-Regulation: Internalizing Discipline Through Culture in an Elementary School - Nursidik; Raharjo; Azam Syukur Rahmatullah; Arina Athiyallah; Lika Hestyaningsih (Psympathic : Jurnal Ilmiah Psikologi, 2026)
Discipline in elementary education is frequently reduced to rule compliance. However, educational psychology views discipline as a developmental process through which externally guided behaviour gradually becomes self-regulation. Limited attention has been given to how this transition is supported through integrated school-culture practices. Therefore, this qualitative instrumental research aimed to examine how the BR3T programme (Bersih/Clean, Rapi/Neat, Tertib/Orderly, Teratur/Regular, Terpelihara/Well-maintained) at SD IT Salsabila, Purworejo, Central Java, functions as a cultural practice that facilitates discipline internalization. Data were collected from 25 participants, including 10 students (Grades 2–6), five homeroom teachers, and ten parents, through non-participant observation, semi-structured interviews, and document analysis. Subsequently, analyses were conducted thematically using Miles, Huberman, and Saldaña's interactive framework. The results showed three interdependent processes, namely (1) behavioural habituation through structured repetition, (2) teacher role modelling that translates routines into moral meaning, and (3) reinforcement through monitoring and reflection that fosters self-evaluation. Collectively, these processes support a gradual shift from supervised compliance toward emerging self-regulation.